Syntactic development in early foreign language learning: Effects of L1 transfer, input, and individual factors - Hopp, Holger; Steinlen, Anja; Schelletter, Christina; Piske, Thorsten (Applied psycholinguistics, 2019)
This study explores parallels and differences in the comprehension of wh-questions and relative clauses between early foreign-language (FL) learners and monolingual children. We test for (a) effects of syntactic first-language (L1) transfer, (b) the impact of input on syntactic development, and (c) the impact of individual differences on early FL syntactic development. We compare the results to findings in child second language (L2) naturalistic acquisition and adult FL acquisition. Following work on adult FL acquisition, we carried out a picture-based interpretation task with 243 child FL learners in fourth grade at different regular, partial, and high-immersion schools in Germany plus 68 monolingual English children aged 5 to 8 years as controls. The child FL learners display a strong subject-first preference but do not appear to use the L1 syntax in comprehension. Input differences across different schools affect overall accuracy, with students at high-immersion FL schools catching up to monolingual performance within 4 years of learning. Finally, phonological awareness is implicated in both early FL learning and naturalistic child L2 development. These findings suggest that early FL development resembles child L2 acquisition in speed and effects of individual factors, yet is different from adult FL acquisition due to the absence of L1 transfer effects.